2022
DOI: 10.1186/s12052-022-00162-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of direct challenges to student endorsement of teleological reasoning on understanding and acceptance of natural selection: an exploratory study

Abstract: Background Teleological reasoning is a cognitive bias purported to disrupt student ability to understand natural selection. Few studies have described pedagogical efforts to decrease student endorsement of teleological reasoning and measure the effects of this attenuation on the understanding and acceptance of evolution. This exploratory study examined the influence of explicit instructional activities directly challenging student endorsement of teleological explanations for evolutionary adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
1
10
0
2
Order By: Relevance
“…However, the aforementioned studies did not investigate the individual effects of different instructional approaches to deal with student conceptions, leaving the question of how best to address intuitive conceptions. Other studies have indicated positive effects of instructional approaches that address students' conceptions such as refutation texts (Pickett et al, 2022), clarifications of misconceptions (Aptyka et al, 2022), discussions about common misconceptions using active learning approaches (Colton et al, 2018), group discussions about styles of scientific explanations (Halls et al, 2021), or direct challenges to intuitive thinking (Wingert et al, 2022). However, no rigorous experimental intervention study exists yet that investigates the effectiveness of specific metaconceptual approaches that are based on self-regulated learning and metacognition and directly address students' intuitive conceptions.…”
Section: Instruction On Conditional Metaconceptual Knowledgementioning
confidence: 99%
“…However, the aforementioned studies did not investigate the individual effects of different instructional approaches to deal with student conceptions, leaving the question of how best to address intuitive conceptions. Other studies have indicated positive effects of instructional approaches that address students' conceptions such as refutation texts (Pickett et al, 2022), clarifications of misconceptions (Aptyka et al, 2022), discussions about common misconceptions using active learning approaches (Colton et al, 2018), group discussions about styles of scientific explanations (Halls et al, 2021), or direct challenges to intuitive thinking (Wingert et al, 2022). However, no rigorous experimental intervention study exists yet that investigates the effectiveness of specific metaconceptual approaches that are based on self-regulated learning and metacognition and directly address students' intuitive conceptions.…”
Section: Instruction On Conditional Metaconceptual Knowledgementioning
confidence: 99%
“…4. Explicación teleológica de la adaptación de los seres vivos, como un proceso dirigido hacia una finalidad (Charrier et al, 2012;González Galli, 2011;González-Galli et al, 2020;Sánchez et al, 2017, Wingert et al, 2022.…”
Section: Explicaciones Sobre La Evoluciónunclassified
“…Así, Hernández et al (2009), sentencian que, un número considerable de estudiantes mantiene concepciones alternativas que no son válidas desde un punto de vista científico, sean de secundaria o universitarios (González Galli, 2011), incluso después de los procesos de enseñanza-aprendizaje. Pérez et al (2018) y Wingert et al (2022), destacan que las principales dificultades son: las creencias religiosas, los obstáculos para el aprendizaje del modelo de evolución por selección natural, entendimiento de escalas temporales, concepciones alternativas incompatibles con los modelos científicos y las ideas del sentido común.…”
Section: Introductionunclassified
“…In recent years, the usage of the I‐SEA has increased (e.g., Barnes et al, 2019, 2020a, 2020b, 2021a, 2021b, 2022b; Ferguson & Jensen, 2021; Fiedler et al, 2019; Hartelt et al, 2022; Rachmatullah et al, 2018; Romine et al, 2018; Sbeglia & Nehm, 2019, 2020; Wingert et al, 2022), and several new insights into the structure of the scales were presented. For example, Sbeglia and Nehm (2019) found that the scales for microevolution and macroevolution are very stable within a university student sample, while the human evolution scale may be split into two sub‐dimensions (i.e., human microevolution and human macroevolution).…”
Section: Measuring Evolution Acceptancementioning
confidence: 99%